An Experimental Study of Compression of Femoral Fractures by an Interlocking Intramedullary Pin - Durall, I.; Diaz, M. C.; Morales, I. (Veterinary and Comparative Orthopaedics and Traumatology, 1993)
Return of function and callus healing were investigated in a group of ten dogs after osteotomy of the femur treated by application of a pin, perfo-rated by threaded openings, through which a metal bar could be introduced into the trochanteric fossa. A jig, indicating the position of the openings, was attached and the distal fragment fixed with three screws into the pin; the fracture was then compressed by means of a compressor travelling from the base of the jig to rest against the bar inserted into the trochanteric fossa, approximating the proximal fragment to the distal one. Two screws were then inserted into the proximal fragment. The results revealed a full return of limb function between four and 16 days and consolidation of the callus between eight and 16 weeks.Femoral osteotomy was performed in a group of ten mongrel dogs weighing between 16 and 32 kg and stabilised with a pin, fixed with screws, which compressed the fracture. The results revealed return of normal limb function between four and 16 days later; consolidation of the callus was complete between eight and 16 weeks.
Keywords: Fracture; compression; pin; interlocking